The promise and perils of debtor-in-possession financing: Lessons from the United States - AYOTTE, Kenneth (Institutional Knowledge at Singapore Management University, 2024)
The ability of viable but financially distressed firms to obtain new financing to keep operating and pursuing value-creating projects is one of the most critical aspects for a successful reorganisation. Unfortunately, when a company becomes insolvent, lenders are rationally skeptical to extend credit. To address this problem, the United States Bankruptcy Code adopted a system, known as debtor-in-possession (‘DIP’) financing, that seeks to encourage lenders to extend credit to financially distressed firms.[1] This is done by providing DIP lenders with different forms of priority that may include a new lien, a junior lien, a senior lien, an administrative expense priority, or an administrative expense priority to be paid ahead of other administrative expenses.[2] Thus, the United States has created a system that can make bankruptcy proceedings serve as liquidity providers for viable but financially distressed firms.[3]As a result of the successful experience of the United States, many countries around the world have adopted (or considered the adoption of) some forms of DIP financing provisions. By analysing the features and evolution of debtor-in-possession financing in the United States, this article seeks to highlight certain risks and challenges associated with a system of DIP financing. It concludes by suggesting various policy recommendations for countries considering the adoption or amendment of DIP financing provisions